Efficacy of Complex Preparation of the Oral Cavity for Orthopedic Treatment - V. M. Soldatyuk; M. M. Rozhko (Galician Medical Journal, 2016)
The article describes a comprehensive approach to preparing patients with dentition defects living in unfavorable environmental conditions for orthopedic treatment as well as the importance of the comprehensive approach including advanced surgical preparation, wider application and proper selection of osteotropic agents, correction with medicines affecting bone tissue regeneration and the course of the postoperative period.